A Metathetic Approach to [5/5/6] Aza-Tricyclic Core of Dendrobine, Kopsanone, and Lycopalhine A Type of Alkaloids - Kotha, Sambasivarao; Pulletikurti, Sunil (Synthesis, 2019)
A concise synthetic approach to [5/5/6] tricyclic pyrrolidine core of dendrobine is reported. This methodology relies on the construction of β-hydroxylactams by NaBH4-I2 reduction followed by reaction of allylsilane with the aid of Lewis acid to generate alkenyl lactams in good yields. Further, ring-opening metathesis (ROM) followed by ring-closing metathesis (RCM) were used to assemble the [5/5/6] aza-tricyclic skeleton of dendrobine. This short synthetic route has been expanded to assemble tricyclic [5/5/8] system with pentenylboronic acid.
Keywords: dendrobine; [5/5/6] aza-tricyclic; metathesis; allylation; NOE; BF3·OEt2